Agricultural Distortions in Sub-Saharan Africa : Trade and Welfare Indicators, 1961 to 2004 - Croser, Johanna L.; Anderson, Kym (World Bank, 2013)
For decades, agricultural price and trade policies in Sub-Saharan Africa hampered farmers' contributions to economic growth and poverty reduction. This paper draws on a modification of so-called trade restrictiveness indexes to provide theoretically precise partial-equilibrium indicators of the trade and welfare effects of agricultural policy distortions to producer and consumer prices in 19 African countries since 1961. Annual time series estimates are provided not only by country but also, for the region, by commodity and by policy instrument. The findings reveal the considerable extent of policy reform over the past two decades, especially through reducing export taxation; but they also reveal that national policies continue to reduce trade and economic welfare much more in Sub-Saharan Africa than in Asia or Latin America.